Parámetros de elaboración mermelada enriquecida de papaya (Carica papaya), mango (Mangifera indica), con camu camu (Myrciaria dubia) - Vargas Ramos, Oscar Cayo (2024)
This research work uses the following raw materials: mango (Mangifera indica), papaya (Carica papaya), and camu camu, the latter being a fruit rich in vitamin C, which adds value to this type of product. These raw materials were acquired from the producers' market and Belén market. The results were taken from the composition tables of the year 2017. The raw materials were then weighed at the pilot plant for canned foods of FIA-UNAP. A standard jam-making process was carried out using these three raw materials, with proportions of mango: papaya: camu camu (1:0.5:0.1). The variables of the study were evaluated (using color, odor, taste, soluble solids, and acidity as variables). Subsequently, physicalchemical tests were conducted, including moisture: 9.27%, titratable acidity (expressed as citric acid): 0.35%, pH (20°C): 3.50, and soluble solids: 65°Brix. Microbiological requirements were also assessed, with results showing fungi (CFU/g): <10 and yeasts (CFU/g): <10. All these controls were performed under the requirements of NTP 203.047-1991 (Revised 2017) and Codex Stan 2962009 for jellies and jams. Finally, sensory evaluation tests were conducted, with respective graphs prepared for each organoleptic evaluation. Subsequently, statistical evaluations of the three treatments (T1, T2, and T3) were performed. It was concluded that, after these tests, including evaluations of color, odor, taste, consistency, and general appearance, there is no significant difference between each treatment conducted.